Sufistic Preaching: a Means of Catharsis for a Psychological Problem - Usep Abdul Matin; Yasmin Kusumawati (JURNAL INDO-ISLAMIKA, 2021)
In his published M.A. thesis, Dakwah Sufistik Kang Jalal Menentramkan Jiwa, Mencerahkan Pikiran (Sufistic/Islamic-Mystical-Dimension Preaching of Mr. Jalal Pacifies the Soul and Enlightens the Mind), Rosyidi does not mention explicitly his key question, his argument, and his hypothesis. However, I grasp them from my reading of this published thesis.